Efficacy and safety of thoracoscopic-guided multiple paravertebral block for video-assisted thoracoscopic lobectomy surgery: a randomized blinded controlled study - Li, Zhixiong; Lin, Qingshui; Lin, Liangqing; Wu, Qinghua; Ke, Pinhui; Chen, Huan; Lin, Chunlan; Yu, Yaohua (Frontiers in Surgery, 2023)
Background Paravertebral block (PVB) has been increasingly popular for postoperative analgesia. However, few studies estimated the efficacy and safety of multiple PVB using thoracoscope-assisted technique for intraoperative analgesia and postoperative pain management for video-assisted thoracoscopic lobectomy (VATS LOBECTOMY). Methods A total of 120 patients scheduled to undergo VATS LOBECTOMY were randomly assigned into two groups: a placebo group and a PVB group in a ratio of 1:2. Thoracoscopic-guided multi-point PVB was carried out with 0.5% ropivacaine (PVB group) or 0.9% NaCl (placebo group) at the beginning and the end of surgery. The primary endpoint was consumption of intraoperative opioid. Results Consumption rate of intraoperative opioids was significantly lower in the PVB group (878.14 ± 98.37 vs. 1,432.20 ± 383.53 for remifentanil; 123.83 ± 17.98 vs. 266.42 ± 41.97 for fentanyl). Postoperatively, significantly longer duration of using patient-controlled intravenous analgesia for the first time, reduced times of analgesic pump pressing, and less rescue analgetic consumption were observed in the PVB group. Visual analog scale scores at rest and during exercising were significantly lower in the PVB group at all time points within the first 48 h after surgery. The PVB group was also associated with significantly higher total QoR-40 scores and lower incidence of analgesia-related adverse events. Conclusions Thoracoscopic-guided multiple PVB was a simple and effective technique in controlling pain both intra- and postoperatively for VATS LOBECTOMY. It was also associated with the absence of detrimental effects attributed to opioid overuse and benefits of the early resumption of activity and physical function recovery. Therefore, this regional anesthesia technique should be advocated as part of a multimodal analgesia protocol for VATS LOBECTOMY.